PEMAHAMAN JURNALISME PROFETIK DALAM REDAKSI WWW.SUARAMUHAMMADIYAH.ID - Andhika Pamungkas (Ekonomi Islam, 2021)
The issuance of Presidential Regulation Number 10 of 2021 concerning the Investment Business Sector, which contains regulations on investment in liquor, has created pros and cons in the community. Most of the people reject the rules that are contrary to Islamic law, some others accept the controversial rules. The issue of rejection of the alcohol investment plan has become news that is widely published by various media, both conventional media and Islamic media. One of them is the official media from the Muhammadiyah Central Executive, www. Suaramuhammadiyah.id. This study seeks to examine the extent to which the concepts and theories of prophetic journalism are understood by the editors of www. Suaramuhammadiyah.id, which are then applied to make news about the rejection of the Presidential Regulation. This study uses a qualitative approach with a descriptive method. Data analysis was carried out by in-depth interviews with key informants and supporting informants with the findings and literature study. The results of this study are expected to determine the extent to which prophetic journalism is understood and applied by the editors of www. Suaramuhammadiyah.id, to carry out bil qalam da'wah through news. Keywords: Suara Muhammadiyah, prophetic journalism, liquor